Prohibition on Choosing Incompetent Leaders: Partial and Simultaneous Analysis of Abu Dzar's History in Sahih Muslim - Nugroho, Nur Abdul Kholik; Damanhuri (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The aim of this research is to conduct a partial and simultaneous analysis of the hadith on the prohibition of electing incompetent leaders. The scope of this research is the main hadith narrated by Abu Dzar. which was takhrij by Imam Muslim. Data relating to hadiths and the quality of each narrator is collected using documentation methods. This type of research is qualitative and data analysis uses content analysis methods. Based on partial analysis, it is found that this hadith is of authentic quality, because (1) All the narrators have the degree of thiqah . (2) Sanad hadith continues. (3) This matan hadith does not contain syadz , because there is no contradiction found with the naqli proposition, namely the Al-Qur'an and Hadith which have a higher sanad quality. (4) This hadith matan does not contain 'illat , because there is no contradiction found with the aqli proposition, namely with common sense, the senses or science. Based on simultaneous analysis; This hadith has 2 tabi ' hadiths. However, because in terms of quality the hadith already has authentic quality, the existence of this tabi'nya hadith has no effect in improving its quality. As for his martyrdom, apparently 6 hadiths of martyrdom were found, this means that the hadiths were narrated by six Companions, namely: Abu Dzar, Abu Hurairah, Auf bin Malik, Zaid bin Thabit, Abu Musa and Abdurrahman bin Samurah.